Music Creations Sabda Hita | Kreasi Musik Sabda Hita - Ida Bagus Gede Angga Prabawa Manuaba (GHURNITA: Jurnal Seni Karawitan, 2023)
Sabda Hita consists of two syllables. Sabda, which means sound or sound produced from friction by humans. While Hita, which means happiness, is owned to achieve prosperity. So broadly speaking, Sabda Hita implies the sound of joy humans create in a harmonious and harmonious relationship. "Sabda Hita" refers to the conception of the teachings of "Tri Hita Karana," which relates to humans and how fellow creatures can live side by side, helping each other create harmonious relationships. Sabda Hita is a musical creation that uses the media, said Gamelan Semar Pegulungan Saih Pitu, which was inspired by three human relations in applying the concept of the teachings of "Tri Hita Karana" for survival in this universe. In creating the Karawitan composition entitled Sabda Hita, Alma M. Hawkins used the method in his book Creating Through Dance (1990), that the arrangement of a work of art is carried out through three stages, namely, Exploration (Exploration), Improvisation, and Forming (formation). This Sabda Hita Karawitan work of art is divided into three parts. Part 1 describes the religious/magical atmosphere associated with the relationship between humans and God. Part 2 describes a beautiful and quiet natural atmosphere when human relations care for each other and the environment. Part 3 describes the atmosphere of happiness associated with human relations among humans, creating happiness and achieving harmonious and harmonious relationships.